1991
DOI: 10.1017/s0317167100031334
|View full text |Cite
|
Sign up to set email alerts
|

Environment, Genetics and Idiopathic Parkinson's Disease

Abstract: ABSTRACT:Since Idiopathic Parkinson's disease (IPD) was first described more than 170 years ago, there have been major advances in the understanding of the etiology of the disease as well as in its treatment. This article will review current knowledge concerning the role of the environment, genetic hypotheses and the aging factor in the etiology of IPD and proposes a complex interaction involving all these factors. Hypotheses regarding mitochondrial inhibition and free radical generation in IPD are discussed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…We appreciate that the intrastriatal 6-OHDA model is not PD however the exact cause of DA neuron degeneration in sporadic PD is currently unknown. Decades of research have indicated that the disease is likely due to cumulative effects of genetic and environmental factors (Elbaz, et al 2007, Migliore and Coppede 2009, Mouradian 2002, Poirier, et al 1991). Oxidative stress has been consistently implicated in contributing to the pathology of PD (Henchcliffe and Beal 2008, Jenner 2007, Przedborski, et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate that the intrastriatal 6-OHDA model is not PD however the exact cause of DA neuron degeneration in sporadic PD is currently unknown. Decades of research have indicated that the disease is likely due to cumulative effects of genetic and environmental factors (Elbaz, et al 2007, Migliore and Coppede 2009, Mouradian 2002, Poirier, et al 1991). Oxidative stress has been consistently implicated in contributing to the pathology of PD (Henchcliffe and Beal 2008, Jenner 2007, Przedborski, et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of PD is thought to involve interplay between environmental agents and genetic risk factors (Poirier et al, 1991,Tsang and Soong, 2003,Allam et al, 2005. A number of inbred strains of mice with differential sensitivity to MPTP have been identified and can be used to identify genetic factors (Hamre et al, 1999,Schwarting et al, 1999,Smeyne et al, 2001,Cook et al, 2003,Liu et al, 2003a,McLaughlin et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Many possible causative factors have been suggest¬ ed, including environmental toxic agents,1 abiotrophy and aging,2 lack of neurotropic hormones,3 genetic defects or genetic predisposition,4 defect of DNA repair mechanism,5 and viral infections.6-7 None of these hypotheses fully ex¬ plains the events responsible for the initiation of PD or identifies its cause. 8 Despite the diffusion of the disease and its impact on public health, comparatively little interest has been direct¬ ed to its epidemiology. Epidemiologie surveys seem to in¬ dicate that PD is less common among nonwhites910 and that the disease is unevenly distributed in Western coun¬ tries.1112 A decreasing north-to-south gradient in mortality has been observed in the United States.10 Annual mortal¬ ity in 33 European and American countries in 1951 through 1958 was between 0.5 and 3.8/100 000.13 An increase in mortality in patients older than 75 years and a decrease in rates in younger subjects has been observed in the United States during the last two decades1415 and also in some Eu¬ ropean countries.16…”
mentioning
confidence: 99%